You are not logged in.

- Topics: Active | Unanswered

**4littlepiggiesmom****Member**- Registered: 2006-01-09
- Posts: 42

(a^-9b^-9)(a^3b^-8)

I* get

a^3/ a^9b^17 which I simpliified to 1/a^6b^17 am I close??

1 more 1/(8xy^-6)^-1 where I get

8xy^6???

Checking my freshman sons homework and he gets something total different......help please:/

Offline

**ryos****Member**- Registered: 2005-08-04
- Posts: 394

(a^-9*b^-9)(a^3*b^-8)

= (1/a^9)(1/b^9)(a^3)(1/b^8)

= 1/(a^6*b^17)

1/(8xy^-6)^-1

= 1 / (y^6/8x)

= 8x/y^6

El que pega primero pega dos veces.

Offline